Phantom Sensations Following Brachial Plexus Nerve Block: A Case Report - Russell, Hannah G.; Tsao, Jack W. (Frontiers in Neurology, 2018)
Following the administration of brachial plexus anesthesia for right thumb carpometacarpal arthroplasty with ligament reconstruction, a 54-year-old woman with all limbs intact developed phantom limb sensations, including the misperception of the placement of her right arm and frozen limb sensations in her fingers. Immobility of her fingers in a stacked position was experienced for approximately 3.5 days after surgery, and she described her phantom sensations as the hand experiencing “tingling” and feeling “heavy”. While the onset of these phantom sensations occurred almost immediately after administration of brachial plexus anesthesia, they lasted for approximately 69 hours after anesthesia wear off, suggesting that cortical effects from denervation resolves much more slowly than initial remapping, giving insight into the mechanisms behind phantom limb sensations that are often experienced by amputees.